2021
DOI: 10.1155/2021/9629718
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Markers and Iron Status of 6–12-Year-Old Thai Children: Associations and Predictors

Abstract: Introduction. Obesity may be associated with poor iron status. The objective of this study was to investigate the association between different indices of iron status and anthropometric measurements in Thai children. Materials and Methods. Anthropometry (weight, height, waist circumference (WC), and body composition assessed by bioelectrical impedance analysis) and iron indices were measured in 336 Thai children aged 6–12 years. Iron deficiency (ID) was defined using two or more of the following: (1) %transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In 2020, the WHO revised their guidance on the use of ferritin to assess iron status in individuals and populations, providing thresholds of <15 µg/L for healthy individuals above 5 years of age and <70 µg/L for individuals with infection or inflammation (<12 µg/L or <30 µg/L are used for children under 5). While current WHO guidance is that ferritin, both an iron storage protein and an acute phase reactant associated with inflammation,43 should not be used alone to diagnose ID without other iron profile biomarkers or corrections for inflammation,44 a minority of studies did rely on ferritin alone 25 45–48. Likewise, serum iron alone should not be used in isolation to diagnose ID as serum iron levels will be reduced in the context of infection or inflammation,49 but was used in a handful of studies 43 50 51.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, the WHO revised their guidance on the use of ferritin to assess iron status in individuals and populations, providing thresholds of <15 µg/L for healthy individuals above 5 years of age and <70 µg/L for individuals with infection or inflammation (<12 µg/L or <30 µg/L are used for children under 5). While current WHO guidance is that ferritin, both an iron storage protein and an acute phase reactant associated with inflammation,43 should not be used alone to diagnose ID without other iron profile biomarkers or corrections for inflammation,44 a minority of studies did rely on ferritin alone 25 45–48. Likewise, serum iron alone should not be used in isolation to diagnose ID as serum iron levels will be reduced in the context of infection or inflammation,49 but was used in a handful of studies 43 50 51.…”
Section: Resultsmentioning
confidence: 99%
“…Inflammatory status is particularly relevant as ferritin, the primary blood biomarker of iron status used, was consistently found higher in obese groups compared with children with normal weight, with direct linear association reported in multiple studies 25 46–49 56 66 85 98–105. However, as ferritin is an acute phase reactant, inflammation can obscure ID106.…”
Section: Discussionmentioning
confidence: 99%
“…Boys experienced muscle growth and changes in BMI as they grew. Studies have found that transferrin receptors increased with BMI [ 35 ], and obese individuals had higher levels of soluble transferrin receptors compared to overweight and normal-weight individuals [ 36 ]. Obesity is associated with chronic inflammation due to the production of pro-inflammatory molecules by adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The public health effects of iron deficiency include reduced work capacity and mental performance, poor growth development, impaired regulation of body temperature, impairments in behaviour and intellectual performance, and decreased resistance to infections [ 13 , 14 ]. Previous studies on the association between different indices of iron status and anthropometric measurements have reported that greater adiposity was associated with poorer iron status, which was demonstrated by lower serum iron (SI) and %transferrin saturation (%Tsat) and higher total iron-binding capacity (TIBC) and soluble transferrin receptor (sTfR) [ 15 ]. Overweight/obese children were also reported to require higher iron intake to maintain their iron homeostasis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the association between different indices of iron status and anthropometric measurements have reported that greater adiposity was associated with poorer iron status, which was demonstrated by lower serum iron (SI) and %transferrin saturation (%Tsat) and higher total iron-binding capacity (TIBC) and soluble transferrin receptor (sTfR) [ 15 ]. Overweight/obese children were also reported to require higher iron intake to maintain their iron homeostasis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%